Pretreatment with or without GnRH-agonist before frozen–thawed embryo transfer in patients with PCOS: a systematic review and meta-analysis - Jie Li; Zhong Lin; Sien Mo; Shujia Wang; Yanmei Li; Qiuling Shi (Journal of Ovarian Research, 2024)
Abstract Purpose This study was aimed to systematically evaluate the efficacy of artificial cycle-prepared frozen–thawed embryo transfer (FET) with or without gonadotrophin-releasing hormone agonist (GnRH-a) pretreatment for women with polycystic ovary syndrome (PCOS). Methods The analysis was carried out by searching the PubMed, EMBASE, and CNKI databases with a combination of keywords before October 2021. The available studies of the effects of GnRH-a pretreatment or no pretreatment on FET in PCOS patients were considered. The risk ratios (RRs) or standardized mean differences (SMD) with 95% confidence intervals (CIs) were calculated with using subgroups and sensitivity analysis. The quality evaluation for this analysis was followed. Results Seventeen studies including 3646 women were analyzed. GnRH-a pretreatment was significantly associated with a higher implantation rate (RR = 1.12, 95%CI: 1.00–1.24) and clinical pregnancy rate (RR = 1.19, 95%CI: 1.08–1.32) than the placebo. Moreover, in the GnRH-a pretreatment group, significant differences were detected for increasing the endometrium thickness among PCOS patients (SMD = 0.56, 95%CI: 0.20–0.92). However, for RCTs subgroup, no differences were observed, even after sensitivity analyses. In addition, the miscarriage rates, ectopic pregnancy rates, multiple pregnancy rates, and live birth rates were similar in both two groups. Conclusions Endometrial preparation using GnRH agonist pretreatment prior to FET seems to be the better choice for PCOS patients. However, well-designed RCTs are required for confirmation.